Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1073/pnas.87.11.4088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of beta-cell glucose transporter gene expression.

Abstract: It has been postulated that a glucose transporter of (3 cells (GLUT-2) may be important In glucosestimulated insulin secretion. To determine whether this transporter is constitutively expressed or regulated, we subjected conscious unrestrained Wistar rats to perturbations in glucose homeostasis and qmntitated (-cell GLUT-2 mRNA by in situ hybridization. After 3 hr of hypoglycemia (glucose at 29 ± 5 mg/dl), GLUT-2 and proinsulin mRNA signal deities were reduced by 25% of the level in control rats. After 4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
40
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 26 publications
9
40
0
Order By: Relevance
“…In contrast, the RNA levels of GLUT2 were slightly increased in 3-to 4-day-old pups lacking IR (Fig. 2B), thereby confirming studies showing that hyperglycemia increases GLUT2 gene expression in ␤-cells (22).…”
Section: Resultssupporting
confidence: 83%
“…In contrast, the RNA levels of GLUT2 were slightly increased in 3-to 4-day-old pups lacking IR (Fig. 2B), thereby confirming studies showing that hyperglycemia increases GLUT2 gene expression in ␤-cells (22).…”
Section: Resultssupporting
confidence: 83%
“…Currently, insulin secretion is known to be stimulated by glucose or its metabolites. In this pathway, GLUT2 may play a role as a glucose sensor (37). Based on these observations and our results, troglitazone is thought not only to protect ␤-cells from lipoapoptosis, but also to improve the glucose sensitivity of ␤-cells.…”
supporting
confidence: 75%
“…Because the GLUT-2 loss coincides temporally with impairment of glucose-stimulated insulin secretion and the onset of hyperglycemia (7,9), it seemed possible that the reduction in GLUT-2 might be the cause of the ␤-cell dysfunction and diabetes (5); however, subsequent studies have indicated that the loss of GLUT-2 is secondary to one or more of the metabolic abnormalities of diabetes, and not their cause (8). Of these metabolic abnormalities, hyperglycemia had been exculpated as the down-regulator of GLUT-2 because it increases, rather than decreases, GLUT-2 expression in normal islets (10). Interest has therefore shifted to a second metabolic abnormality of diabetes, high plasma free fatty acid (FFA) levels (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%